Andrographis paniculata: A potential supplementary therapy for cardiovascular diseases - A systematic review of its effects and molecular actions - Oluebube Magnificient Eziefule; Wawaimuli Arozal; Septelia Inawati Wanandi; Syarifah Dewi; Nafrialdi; Meilania Saraswati; Melva Louisa (GarVal Editorial Ltda., 2024)
Context: Cardiovascular diseases claim the lives of an estimated 17.9 million people worldwide (report by the World Health Organization), yet the drug pipeline compared to some other life-threatening diseases, including cancer and neurological disorders, is low. Aims: To investigate the potential of Andrographis paniculata as a supplementary therapy for cardiovascular diseases based on recent in vivo animal studies. Methods: This study adopted a systematic review approach to analyze preclinical evidence from in vivo animal studies. Three databases (PubMed, Scopus, and Embase) were searched using the keywords "Andrographis paniculata", "cardiovascular disease", "CVD", "heart disease", "cardioprotective", "cardio*", "inflammation", "oxidative stress", "obesity", "lipopolysaccharide", "hypertension", "arrhythmia" and "aortic disease". The search period was from April 20th, 2023, to April 26th, 2023, and included studies published from 2013 to 2023. Only in vivo animal studies were appraised. In contrast, clinical studies, in vitro studies, in silico studies, and review papers were excluded. SYRCLE's risk of bias tool was used to assess the risk of bias. Results: Sixteen eligible in vivo animal studies showed that Andrographis paniculata extracts and isolated bioactive compounds have strong anti-inflammatory and antioxidant effects on cardiovascular diseases. These effects lead to lowering the risk of coronary artery disease and myocardial infarction, easing the effects of bad cardiac remodeling, stopping cardiac hypertrophy, and improving diabetic cardiomyopathy. Although SYRCLE's tool detected some bias, the studies were included since they met the inclusion criteria and had no conflicts of interest. Conclusions: Andrographis paniculata may have the potential to be used as a supplementary therapy for cardiovascular diseases, but more animal studies and clinical trials should be done to establish these findings.